Mondo di donne, mondo di parole Espressione linguistica della condizione femminile in Tutto su mia nonna di Silvia Ballestra - Janusz, Joanna (Romanica Silesiana)
The feminine world, the world of words. The linguistic expression of the feminine condition in Tutto su mia nonna by Silvia Ballestra The novel Tutto su mia nonna by Silvia Ballestra is the excellent example of language, writing and sensibility straightforwardly feminine. The main characters of the narration that is the three generations of woman, become the vivid and active subjects of the narration, who form the reality, non only filtering the world which is being narrated in their personal emotional way, but also structuring their world in relationship to the social existence as though their activity does not refer only to their private and personal zone. The definition of femininity passes through the language as it is not only the way to comunicate but it assumes three different manners: conative, magical and sensual. The sensual and tangible aspect values, by the use of marchigiano dialect, the material, concrete meaning that refers to the body and its physical expression. The magical and commemorative function is proper of the everyday language and it pushes the main character, the narrator to immerge in the recollections of the past that is rituals and old habits of the family. The most important function though is the conative one, which focuses on the interpersonal contact assuming the real communicative function that brings the family together.In this way the language becomes a treasure, a connection and a relationship. As for the formal level of writing, the interlocutory discourse is maintained by the use of the pronoun tu that refers to the reader who participates in the narration that touches more subjects in the narrative passages and in those of the philosophical and the metanovelistic kind as well. Key words: Silvia Ballestra, feminine writing, dialect, conative value, dialogue.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />